A preparation method of metal oxide modified attapulgite adsorbent for removing organic nitrides
By loading metal oxides on the bump soil, a highly efficient adsorption agent is prepared, the problem of difficulty removing organic nitrogen in the catalyst in the existing technology has been solved, and the efficient adsorption of the organic compounds of a variety of nitrogen categories is realized. Stable operation.
Patent Information
- Application Number
- CN202310026463.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-01-09
AI Technical Summary
The prior art is difficult to effectively remove organic nitrides, especially alkaline nitrides present in catalytic cracking, catalytic reforming and light chain alkane dehydrogenation devices, resulting in reduced catalyst activity and unstable device operation.
By modified by the uneven rod soil with metal oxides (such as COO, CUO), the uneven soil adsorbent of the load metal oxide is prepared. This adsorbent is prepared through the crystal reaction steps in the pickled and high -pressure reactive kettle, which can make high -efficiency adsorption of alkaline and non -alkaline nitrogen organic compounds.
The efficient adsorption rate of non -alkaline nitrogen organic compounds such as pyridine, pyrine, pyrine, and aniline, and non -alkaline nitrogen organic compounds such as pyrodia, pagrazole, pyrodinate, etc., reached 99%, and low raw materials and low preparation costs. Have good industrial application prospects.
Smart Images

Figure CN115888635B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of adsorbent materials, and in particular relates to a method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides. Background Art
[0002] There are trace amounts of nitrides in the raw materials used in catalytic cracking, catalytic reforming, light-chain alkane dehydrogenation and other devices, mainly in the form of pyridine, quinoline, aniline, indole, carbazole, pyrrole and other compounds and their derivatives. Nitrides will generate ammonia in a high-temperature catalytic environment, and ammonia reacts with hydrogen chloride to generate ammonium chloride salts, which block the internal pores of the catalyst, causing the catalyst activity to decrease and making it difficult to remove; most of the catalysts used in catalytic cracking, catalytic reforming, and light-chain alkane dehydrogenation devices contain aluminum elements, and aluminum atoms contain empty orbitals, and nitrogen atoms have a pair of lone pairs of electrons. All nitrides are easily chemically adsorbed on the surface of the catalyst carrier, hindering the adsorption of the reaction substrate, thereby causing the catalyst to be temporarily poisoned; in addition, alkaline nitrides will neutralize the acidity of the catalyst, promote the formation of coke, and reduce the activity of the catalyst. Therefore, it is necessary to remove the nitrides in the raw materials to ensure efficient and stable operation of the device.
[0003] The hydrodenitrogenation process is the most widely used traditional denitrification method. The catalytic hydrodenitrogenation of organic nitrogen compounds requires high temperature and high pressure reaction conditions, and requires a large amount of hydrogen. Due to the high cost, high risk and high energy consumption of this process, it is gradually being replaced by the adsorption denitrification process.
[0004] The adsorbents currently under study are mostly used to adsorb alkaline organic nitrogen compounds, such as pyridine, quinoline, aniline, etc. The removal of nitrogen compounds is achieved by changing or increasing the acidity expression of the adsorbent and undergoing acid-base neutralization reaction with the alkaline nitrogen compounds. The adsorption performance of the adsorbent is positively correlated with the number of acidic sites carried by the adsorbent.
[0005] Chinese patent CN104232149A discloses "a material for efficiently removing alkaline nitrides from oil products". Graphite is modified to produce carboxyl functional groups on its surface, which has good adsorption properties for quinoline and its derivatives. However, the mechanical strength of graphite is poor and it is difficult to meet the needs of large-scale industrial production.
[0006] Chinese patent CN104998606A discloses "an adsorbent for removing non-alkaline nitrides from hydrocarbon products and its preparation method", which uses aluminum oxide and silicon oxide as carriers, loads copper salts, and obtains the finished adsorbent through calcination, reduction and other steps. It has a good removal effect on pyrrole and its derivatives in alkanes. However, the inventors did not study the adsorption performance of the adsorbent on alkaline nitrides.
[0007] There are also a small number of literature reports on broad-spectrum adsorbents that can adsorb organic nitrogen compounds, but due to their high preparation costs, complicated processes, and low adsorption efficiency, their prospects for industrial application are slim.
[0008] Therefore, in the process of removing organic nitrogen from hydrocarbons, finding an adsorbent with a wide range of adsorption types, low preparation cost and high adsorption efficiency is a bottleneck that needs to be solved urgently. The theoretical chemical structure of attapulgite (ATP) is (Al2Mg2)Si8O 20 (OH)2(OH2)4·4H2O is a hydrated magnesium silicate clay mineral with an intermediate structure between the chain structure and the layered structure. It has certain ion exchange properties and a high specific surface area. It is often used as a heavy metal adsorbent or catalyst carrier, but there is no literature report on the adsorption of nitrogen organic compounds in hydrocarbons. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides, and to obtain a metal oxide modified attapulgite adsorbent, which can adsorb both basic nitrogen organic compounds and non-basic nitrogen organic compounds, with an adsorption rate of up to 99%. Moreover, the raw material price is low, the preparation cost is low, and it has a good industrial application prospect.
[0010] The technical solution of the present invention is as follows:
[0011] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0012] 1) placing attapulgite in an acid solution for pickling at a temperature of 40 to 80° C. for 1 to 3 h, filtering and washing until the pH of the supernatant is neutral, and vacuum drying at 40 to 80° C. to obtain a solid product;
[0013] 2) dissolving the solid product obtained in step 1) with a surfactant and a metal salt in an ethanol solution with a mass fraction of 50 to 95% to obtain a mixed solution, adjusting the pH value of the mixed solution to 9 to 12 with an alkali solution, and then placing the mixed solution in a high-pressure reactor for a crystallization reaction;
[0014] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until the pH of the supernatant is neutral, and then vacuum dried at 40-80° C. and calcined to obtain a metal oxide modified attapulgite adsorbent.
[0015] Preferably, in step 1), the acidic solution is one of hydrochloric acid solution, nitric acid solution, phosphoric acid solution and sulfuric acid solution, preferably nitric acid solution.
[0016] Preferably, in step 1), the concentration of the acidic solution is 3 to 5 mol / L.
[0017] Preferably, in step 1), the ratio of attapulgite to acidic solution is 1 g: 10-50 mL.
[0018] Preferably, in step 2), the surfactant is one of P123, F108, polyethylene glycol-2000, polyethylene glycol-4000, 18-crown ether-6, hexadecyltrimethylammonium bromide, and trioctylmethylammonium chloride.
[0019] Preferably, in step 2), the metal salt is any two of molybdenum trichloride, cadmium nitrate tetrahydrate, nickel nitrate hexahydrate, cobalt nitrate hexahydrate, cupric chloride dihydrate, and cerium nitrate hexahydrate, preferably cobalt nitrate hexahydrate and cupric chloride dihydrate.
[0020] Preferably, in step 2), the molar mass ratio of the attapulgite, surfactant, cobalt nitrate hexahydrate and cupric chloride dihydrate is 1:(0.01-0.05):(0.3-0.6):(0.3-0.6).
[0021] Preferably, in step 2), the alkali solution is one of potassium hydroxide solution, sodium hydroxide solution, ammonia water, and sodium carbonate solution, preferably ammonia water.
[0022] Preferably, in step 2), the crystallization reaction temperature is 120-160° C., and the crystallization reaction time is 24-48 hours.
[0023] Preferably, in step 3), the calcination conditions are: heating to 450-600° C. at a heating rate of 1-3° C. / min and calcining for 2-5 hours.
[0024] The present invention innovatively proposes to use attapulgite as the base material, introduce metal oxides for modification, and prepare attapulgite adsorbent loaded with metal oxides, which has a good adsorption effect on both alkaline and non-alkaline nitrogen organic chemicals. This is because there are abundant hydroxyl groups in the structure of attapulgite (ATP) to form Bronsted acid sites, Al 3+ Lewis acid sites are formed, which have good adsorption properties for nitrogen organic compounds.
[0025] Metal oxides, such as CoO and CuO, are loaded on the surface of attapulgite with good dispersion, and combined with the chain channels of the attapulgite layer to enhance the fixation of nitrides on the surface of attapulgite. In addition, the addition of CoO and CuO enables the attapulgite to expose more adsorption active sites, which is beneficial to improving the adsorption capacity of nitrides.
[0026] The beneficial effects of the present invention are:
[0027] The present invention loads metal oxides on attapulgite to enhance the fixation of nitrides on the surface of the attapulgite. At the same time, the addition of metal oxides enables the attapulgite to expose more adsorption active sites, which is beneficial to improving the adsorption capacity of nitrides.
[0028] The adsorbent prepared by the present invention has good adsorption performance for basic nitrogen organic compounds such as pyridine, quinoline, aniline, and non-basic nitrogen organic compounds such as indole, carbazole, pyrrole, and the like, with an adsorption rate of up to 99%. In addition, the raw material price is low, the preparation cost is low, and it has a good industrial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A graph showing the variation of the adsorption rate of nitride by the adsorbent prepared in Example 1 of the present invention over time. DETAILED DESCRIPTION
[0030] The present invention is further described below through specific embodiments and drawings, but the embodiments do not limit the protection scope of the present invention.
[0031] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all commonly used methods in the art unless otherwise specified.
[0032] Unless otherwise specified, the reagents used in the following examples can be purchased from conventional biochemical reagent stores.
[0033] Example 1
[0034] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0035] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a nitric acid solution with a concentration of 3 mol / L, and the ratio of attapulgite to the acidic solution is 1 g: 20 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 60° C. for 3 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 50° C., and grinding to obtain a solid product for standby use;
[0036] 2) dissolving the solid product obtained in step 1) and hexadecyltrimethylammonium bromide in 100 mL of 75% ethanol solution, adding cobalt nitrate hexahydrate and copper chloride dihydrate, and adjusting the pH to 10 with 25% ammonia water until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 150° C. for reaction for 36 hours; wherein the molar mass ratio of attapulgite, hexadecyltrimethylammonium bromide, cobalt nitrate hexahydrate, and copper chloride dihydrate is 1:0.01:0.5:0.5;
[0037] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 50°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 550°C at a heating rate of 3°C / min and kept at a constant temperature for 3h to obtain a CoO-CuO / ATP adsorbent.
[0038] Adsorbent adsorption nitride performance evaluation test:
[0039] 10g CoO-CuO / ATP adsorbent was weighed, crushed into 20 mesh particles and placed in the constant temperature area in the middle of the tubular fixed bed. The rest of the space was filled with quartz sand and quartz wool. The adsorbed mixture model consisted of pyridine, aniline, indole, and carbazole dissolved in cyclohexane with a mass concentration of 1g / L. The adsorption temperature was 30℃, the adsorption pressure was 1.0MPa, and the liquid hourly space velocity was 10h -1 The adsorbed mixture was transported to the fixed bed by a high-pressure constant-current micropump, and the outlet of the fixed bed was connected to a gas chromatograph to analyze the nitride content. After one hour of adsorption, the adsorption rate was calculated to be 99.5%.
[0040] Example 2
[0041] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0042] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a nitric acid solution with a concentration of 5 mol / L, and the ratio of attapulgite to the acidic solution is 1 g: 20 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 50° C. for 3 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 50° C., and grinding to obtain a solid product for standby use;
[0043] 2) dissolving the solid product obtained in step 1) and hexadecyltrimethylammonium bromide in 100 mL of 95% ethanol solution, adding cobalt nitrate hexahydrate and copper chloride dihydrate, and adjusting the pH to 12 with 25% ammonia water until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 150° C. for reaction for 36 hours; wherein the molar mass ratio of attapulgite, hexadecyltrimethylammonium bromide, cobalt nitrate hexahydrate, and copper chloride dihydrate is 1:0.03:0.5:0.4;
[0044] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 50°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 550°C at a heating rate of 2°C / min and kept at a constant temperature for 3h to obtain a CoO-CuO / ATP adsorbent.
[0045] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.3%.
[0046] Example 3
[0047] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0048] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a phosphoric acid solution with a concentration of 3 mol / L, and the ratio of attapulgite to the acidic solution is 1 g: 20 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 60° C. for 3 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 50° C., and grinding to obtain a solid product for standby use;
[0049] 2) dissolving the solid product obtained in step 1) and polyethylene glycol-2000 in 100 mL of 75% ethanol solution by mass, adding cobalt nitrate hexahydrate and cadmium nitrate tetrahydrate, and adjusting the pH to 10 with 25% ammonia water until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 160° C. to react for 24 hours; wherein the molar mass ratio of attapulgite, polyethylene glycol-2000, cobalt nitrate hexahydrate, and cadmium nitrate tetrahydrate is 1:0.01:0.5:0.5;
[0050] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 40°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 600°C at a heating rate of 3°C / min for 2h to obtain a CoO-CdO / ATP adsorbent.
[0051] The performance evaluation test of the adsorbent for adsorbing nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.6%.
[0052] Example 4
[0053] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0054] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a nitric acid solution with a concentration of 5 mol / L, and the ratio of attapulgite to the acidic solution is 1 g:10 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 80° C. for 2 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 60° C., and grinding to obtain a solid product for standby use;
[0055] 2) The solid product obtained in step 1) and F108 are dissolved in 100 mL of 75% ethanol solution, and nickel nitrate hexahydrate and cupric chloride dihydrate are added. After they are completely dissolved, the pH value is adjusted to 10 with 25% ammonia water, and then the mixed solution is placed in a high-pressure reactor and placed in an oven at 150° C. for reaction for 36 hours; wherein the molar mass ratio of attapulgite, F108, nickel nitrate hexahydrate, and cupric chloride dihydrate is 1:0.05:0.6:0.3;
[0056] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 80°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 600°C at a heating rate of 3°C / min for 3h to obtain a NiO-CuO / ATP adsorbent.
[0057] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.3%.
[0058] Example 5
[0059] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0060] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a hydrochloric acid solution with a concentration of 3 mol / L, and the ratio of attapulgite to the acidic solution is 1 g:30 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 40° C. for 3 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 80° C., and grinding to obtain a solid product for standby use;
[0061] 2) dissolving the solid product obtained in step 1) and hexadecyltrimethylammonium bromide in 100 mL of 90% ethanol solution by mass, adding nickel nitrate hexahydrate and cadmium nitrate tetrahydrate, and adjusting the pH to 9 with 25% ammonia water until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 120° C. to react for 48 hours; wherein the molar mass ratio of attapulgite, hexadecyltrimethylammonium bromide, nickel nitrate hexahydrate, and cadmium nitrate tetrahydrate is 1:0.01:0.6:0.6;
[0062] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 50°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 550°C at a heating rate of 3°C / min and kept at a constant temperature for 3h to obtain a NiO-CdO / ATP adsorbent.
[0063] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.7%.
[0064] Example 6
[0065] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0066] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a nitric acid solution with a concentration of 3 mol / L, and the ratio of attapulgite to the acidic solution is 1 g:50 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 80° C. for 1, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 40° C., and grinding to obtain a solid product for standby use;
[0067] 2) dissolving the solid product obtained in step 1) and 18-crown ether-6 in 100 mL of 60% ethanol solution by mass, adding cobalt nitrate hexahydrate and molybdenum trichloride, and adjusting the pH to 12 with 25% sodium carbonate solution until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 160° C. for reaction for 24 hours; wherein the molar mass ratio of attapulgite, 18-crown ether-6, cobalt nitrate hexahydrate, and molybdenum trichloride is 1:0.05:0.3:0.3;
[0068] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 40°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 450°C at a heating rate of 1°C / min for 5 hours to obtain a CoO-Mo2O3 / ATP adsorbent.
[0069] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.0%.
[0070] Example 7
[0071] A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides comprises the following steps:
[0072] 1) placing attapulgite in an acidic solution for pickling, wherein the acidic solution is a sulfuric acid solution with a concentration of 3 mol / L, and the ratio of attapulgite to the acidic solution is 1 g:50 mL, placing the attapulgite in a magnetic stirring water bath, stirring at a constant temperature of 70° C. for 2 h, filtering and washing until the pH of the supernatant is neutral, placing the filter cake in a vacuum drying oven, vacuum drying at 40° C., and grinding to obtain a solid product for standby use;
[0073] 2) dissolving the solid product obtained in step 1) and trioctylmethylammonium chloride in 100 mL of 50% ethanol solution by mass, adding cerium nitrate hexahydrate and copper chloride dihydrate, and adjusting the pH to 10 with 25% ammonia water until they are completely dissolved, and then placing the mixed solution in a high-pressure reactor and placing it in an oven at 140° C. for reaction for 36 hours; wherein the molar mass ratio of attapulgite, trioctylmethylammonium chloride, cerium nitrate hexahydrate, and copper chloride dihydrate is 1:0.04:0.6:0.6;
[0074] 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until it is neutral, and vacuum dried at 60°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 550°C at a heating rate of 2°C / min and kept at a constant temperature for 4h to obtain a CeO2-CuO / ATP adsorbent.
[0075] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 99.3%.
[0076] Comparative Example 1
[0077] A preparation and application of a metal oxide modified attapulgite adsorbent for removing organic nitrides, the specific steps are:
[0078] (1) Weigh a certain amount of attapulgite and hexadecyltrimethylammonium bromide and add them to 100 mL of 75% ethanol solution, stir at room temperature for 30 minutes, then weigh a certain amount of cobalt nitrate hexahydrate and cupric chloride dihydrate and dissolve them therein, continue stirring at room temperature for 60 minutes, the molar mass ratio of attapulgite, hexadecyltrimethylammonium bromide, cobalt nitrate hexahydrate and cupric chloride dihydrate is 1:0.01:0.5:0.5, and then adjust the pH value with 25% ammonia water. When the temperature reaches about 10, pour it into a crystallization reactor with a polytetrafluoroethylene liner, place it in a 150°C oven to react for 36 hours, skim off the upper layer of water, wash and centrifuge the settled solid until the pH value is close to neutral, put the filter cake into a vacuum drying oven, and dry it at a constant temperature of 50°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature at a heating rate of 3°C / min to 550°C and kept at a constant temperature for 3 hours to obtain CoO-CuO / ATP adsorbent.
[0079] The adsorbent's performance evaluation test on adsorption of nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 80.9%.
[0080] Comparative Example 2
[0081] A preparation and application of a metal oxide modified attapulgite adsorbent for removing organic nitrides, the specific steps are:
[0082] (1) According to the ratio of attapulgite to solvent: 1 g: 20 mL, a certain mass of attapulgite is weighed and poured into 200 mL of 3 mol / L nitric acid solution, placed in a magnetic stirring water bath, stirred at 60°C for 3 h, filtered, and the filter cake is washed with deionized water until it is nearly neutral. The filter cake is placed in a vacuum drying oven, dried at 50°C, and ground into powder for later use.
[0083] (2) Weigh a certain mass of acid-treated attapulgite and hexadecyltrimethylammonium bromide and add them to 100 mL of 75% ethanol solution, stir at room temperature for 30 minutes, the molar mass ratio of attapulgite and hexadecyltrimethylammonium bromide is 1:0.01, and then adjust the pH value to about 10 with 25% ammonia water, pour it into a crystallization reactor with a polytetrafluoroethylene liner, place it in a 150°C oven to react for 36 hours, skim off the upper layer of clear water, wash and centrifuge the solid until the pH value is close to neutral, put the filter cake into a vacuum drying oven, and dry it at a constant temperature of 50°C. The dried solid is crushed, poured into a crucible, and placed in a muffle furnace for calcination. The calcination conditions are: from room temperature to 550°C at a heating rate of 3°C / min and kept at a constant temperature for 3 hours to obtain the treated ATP adsorbent.
[0084] The performance evaluation test of the adsorbent for adsorbing nitrides was the same as in Example 1. After one hour of adsorption, the calculated adsorption rate was 72.2%.
[0085] Figure 1 The graph of the adsorption rate of nitrides prepared by the adsorbent in Example 1 of the present invention over time. It can be seen from the graph that the adsorption rate of the metal oxide modified attapulgite adsorbent prepared by the present invention is above 99% before 300 minutes; the adsorption rate slowly decreases after 300 minutes, and the adsorption rate can be maintained above 95% within the 450 minutes of the investigation, indicating that the metal oxide modified attapulgite adsorbent prepared by the present invention has the advantages of high adsorption rate and long stable adsorption performance for nitrides.
[0086] It can be seen from the above embodiments and comparative examples that the attapulgite clay modified by adding cobalt oxide and aluminum oxide has a high adsorption rate for both alkaline nitride and neutral nitride.
[0087] In this specification, various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
Claims
1. A method for preparing a metal oxide modified attapulgite adsorbent for removing organic nitrides, characterized in that: The steps include: 1) The attapulgite is placed in an acid solution for pickling at a temperature of 40-80°C for 1-3 hours, filtered and washed until the pH of the supernatant is neutral, and vacuum dried at 40-80°C to obtain a solid product; 2) dissolving the solid product obtained in step 1) with a surfactant and a metal salt in an ethanol solution with a mass fraction of 50-95% to obtain a mixed solution, adjusting the pH value of the mixed solution to 9-12 with an alkali solution, and then placing the mixed solution in a high-pressure reactor for a crystallization reaction; The metal salt is cobalt nitrate hexahydrate and copper chloride dihydrate, cerium nitrate hexahydrate and copper chloride dihydrate, cobalt nitrate hexahydrate and cadmium nitrate tetrahydrate, nickel nitrate hexahydrate and copper chloride dihydrate, nickel nitrate hexahydrate and cadmium nitrate tetrahydrate, or cobalt nitrate hexahydrate and molybdenum trichloride; 3) After the crystallization reaction is completed, the solid obtained after centrifugation is washed with clean water until the pH of the supernatant is neutral, and then vacuum dried at 40-80°C and calcined to obtain a metal oxide modified attapulgite adsorbent.
2. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 1), the acidic solution is one of hydrochloric acid solution, nitric acid solution, phosphoric acid solution and sulfuric acid solution.
3. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 1), the acidic solution is a nitric acid solution.
4. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrides according to claim 1, 2 or 3, characterized in that: In step 1), the concentration of the acidic solution is 3-5 mol / L.
5. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrides according to claim 1, 2 or 3, characterized in that: In step 1), the ratio of attapulgite to acidic solution is 1 g: 10-50 mL.
6. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 2), the surfactant is one of P123, F108, polyethylene glycol-2000, polyethylene glycol-4000, 18-crown ether-6, hexadecyltrimethylammonium bromide, and trioctylmethylammonium chloride.
7. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 2), the metal salts are cobalt nitrate hexahydrate and cupric chloride dihydrate.
8. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 6, characterized in that: In step 2), the molar mass ratio of the attapulgite, the surfactant, the cobalt nitrate hexahydrate and the cupric chloride dihydrate is 1:(0.01-0.05):(0.3-0.6):(0.3-0.6).
9. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 2), the alkali solution is one of potassium hydroxide solution, sodium hydroxide solution, ammonia water and sodium carbonate solution.
10. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 9, characterized in that: In step 2), the alkali solution is aqueous ammonia.
11. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 2), the crystallization reaction temperature is 120-160° C., and the crystallization reaction time is 24-48 hours.
12. The method for preparing the metal oxide modified attapulgite adsorbent for removing organic nitrogen compounds according to claim 1, characterized in that: In step 3), the calcination conditions are: heating to 450-600°C at a heating rate of 1-3°C / min and calcining for 2-5h.
13. The metal oxide modified attapulgite adsorbent prepared by the method according to any one of claims 1 to 12 is used for removing organic nitrogen compounds.
Citation Information
Patent Citations
Material for efficiently removing basic nitrogen compounds in oils
CN104232149A
Adsorbent for removing non-basic nitrides from hydrocarbon products and preparation method thereof
CN104998606A
Method for preparing magnetic attapulgite clay loaded with composite photocatalyst
CN106179521A